Effects of Soybean Processing and Packaging on the Quality of Commonly Consumed Local Delicacy Tempe - Santhirasegaram, V.; George, D.S.; Anthony, K.K.; Singh, H.K.B.; Saruan, N.M.; Razali, Z.; Somasundram, C. (Wiley, 2016)
Tempe is a processed food, produced by fermenting soybeans with fungus Rhizopus oligosporus. In this study, the effects of soybean processing (soaking, cooking and fermentation) and packaging (food grade wrapping paper, polyethylene bags and low density polyethylene cling wrap) on physicochemical properties, antioxidant activities and microbial count were evaluated. In addition, shelf life study of tempe samples (packed) was conducted for 1 week. Soaking and cooking significantly decreased polyphenols, flavonoids and antioxidant activities of soybeans. After fermentation, tempe samples exhibited significant improvement in physicochemical properties, antioxidant activities and extractability of polyphenols and flavonoids, when compared with unfermented soybeans. Food grade wrapping paper and perforated polyethylene bags were selected as suitable materials for packaging tempe as there were no significant changes in quality and the shelf life of tempe was extended for 3 days. Results obtained support the use of fermentation to improve the quality of soybeans along with safety standards. Practical Applications: Tempe processing and packaging plays an important role in extending the shelf-life of the product. The results of this study suggest that tempe samples exhibited significant improvement in antioxidant activities and extractability of polyphenols and flavonoids, after fermentation. Food grade wrapping paper and perforated polyethylene bags were selected as suitable materials for packaging tempe. This study could serve to improve the progress of processing and packaging for maintaining the quality of tempe.